The differences of orthodontic tooth movement on menstrual and ovulation cycle - Sonya Grecila Susilo; Rahmi Amtha; Boedi Oetomo Roeslan; Joko Kusnoto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Estrogens are sex hormon that play an important role in bone metabolism, including in bone remodeling during orthodontic treatment. Women has a monthly cycle which is affected by fluctuations of estrogen that is menstruation and ovulation. Purpose: The study was aimed to determine the differences of orthodontic tooth movement during menstrual an ovulation cycle. Methods: Five women were given ± 100 g orthodontic force using fixed orthodontic appliance with straight wire technique at the time of menstruation and ovulation with an interval of 1.5 months. Orthodontic tooth movement and levels of estrogen were measured during menstruation and ovulation. Results: Statistical results showed a significant differences between estrogen levels and orthodontic tooth movement (p < 0.05). When estrogen levels decline as in menstruation, tooth movement as results of orthodontic force would increase, whereas when estrogen levels increase as the time of ovulation, tooth movement would decrease. Conclusion: The estrogen level in menstruation and ovulation cycle may affect the tooth movement on ortodontic treatment.Latar belakang: Estrogen merupakan hormon seks yang mempunyai peran penting dalam metabolisme tulang termasuk dalam remodeling tulang selama perawatan ortodonti. Wanita memiliki siklus bulanan yang dipengaruhi oleh fluktuasi estrogen yaitu menstruasi dan ovulasi. Tujuan: Penelitian ini bertujuan untuk mengetahui perbedaan pergerakan gigi akibat gaya ortodonti pada siklus menstruasi dan ovulasi. Metode: Lima orang wanita diberikan gaya ortodonti ±100 gr menggunakan alat orthodontik cekat dengan teknik straight wire pada saat menstruasi dan ovulasi dengan selang waktu 1,5 bulan. Selain itu subyek juga diukur kadar estrogennya saat menstruasi dan ovulasi. Hasil: Hasil statistik menunjukan kadar estrogen berbanding terbalik dengan pergerakan gigi ortodonti (p < 0,05). Saat kadar estrogen menurun seperti pada menstruasi, maka pergerakan gigi akan meningkat, sedangkan pada saat kadar estrogen meningkat seperti saat ovulasi, maka pergerakan gigi akan menurun. Simpulan: Kadar estrogen pada siklus menstruasi dan ovulasi dapat mempengaruhi pergerakan gigi pada perawatan ortodonti.